2017
DOI: 10.1177/0267659117742479
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Lyte 148 vs. Hartmann’s solution for cardiopulmonary bypass pump prime: a prospective double-blind randomized trial

Abstract: During CPB, PL and HS did not cause a significant metabolic acidosis. There was hyperacetatemia and hypergluconatemia with PL and hyperchloremia and hyperlactatemia with HS. These physiochemical effects appear clinically innocuous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Since this survey was conducted, Weinberg et al 8 have published an investigation on the incidence of either a Plasma-Lyte or Hartmann's prime solution in causing metabolic acidosis on bypass. The conclusion to this study was that neither solution produced a metabolic acidosis at the bypass time of 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this survey was conducted, Weinberg et al 8 have published an investigation on the incidence of either a Plasma-Lyte or Hartmann's prime solution in causing metabolic acidosis on bypass. The conclusion to this study was that neither solution produced a metabolic acidosis at the bypass time of 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, metabolic acidosis has not been shown at the end of bypass with either Plasma-Lyte or Hartmann's solution in the modern context. 8 Mannitol is reported to be beneficial for maintaining osmotic pressure, renal function and fluid balance. 1,6 A total of 19 (30%) units add mannitol with the intent to achieve this benefit and more.…”
Section: Discussionmentioning
confidence: 99%
“…It was gratifying to read Weinberg and colleagues' study comparing the effects of two crystalloid solutions on acid-base balance as there is insufficient evidence of the effects of priming solutions used for cardiopulmonary bypass (CPB) on the outcome from cardiac surgery. 1 We have noted the important contribution of the effects of disturbances in strong ion difference caused by priming solutions on acid-base balance. 2 Indeed, we have noted the important effects of changing of the prime from Ringer's to Hartmann's solutions.…”
Section: Sirmentioning
confidence: 99%
“…During our literature search for the review, we identified Weinburg and colleagues' paper comparing Plasma-Lyte 148 and Hartmann's solutions for priming cardiopulmonary bypass (CPB) circuits. 1 Although the primary direction of their randomised controlled trial was to examine the effect on acid-base balance, it reports some very important information as to the effects of priming solutions on blood calcium levels.…”
Section: Sirmentioning
confidence: 99%